2017
DOI: 10.1007/s12072-017-9800-7
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive serum models to predict significant liver related events in chronic hepatitis C

Abstract: Some simple pretreatment blood parameters and NIFS showed high accuracy for predicting development of SLRE post treatment. Application of these simple scores can improve assessment of long-term liver prognosis for CHC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 31 publications
0
14
2
Order By: Relevance
“…Different serum biomarkers have been retrospectively analysed, in all cases without any correlation with histology, and studies provided discordant results. In fact, Toyoda and colleagues found that low pre‐treatment Forns Score values were protective against the risk of liver cancer, whereas none of the 20 tests analysed in the study by Thandassery et al reached any significant predictive value at multivariate analysis . On the contrary, we found that Forns Score, Lok Index and PLF values above the viremic F4 cut‐off were associated with an increased risk of HCC.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…Different serum biomarkers have been retrospectively analysed, in all cases without any correlation with histology, and studies provided discordant results. In fact, Toyoda and colleagues found that low pre‐treatment Forns Score values were protective against the risk of liver cancer, whereas none of the 20 tests analysed in the study by Thandassery et al reached any significant predictive value at multivariate analysis . On the contrary, we found that Forns Score, Lok Index and PLF values above the viremic F4 cut‐off were associated with an increased risk of HCC.…”
Section: Discussioncontrasting
confidence: 72%
“…In fact, Toyoda and colleagues 38 found that low pre-treatment Forns Score values were protective against the risk of liver cancer, whereas none of the 20 tests analysed in the study by Thandassery et al reached any significant predictive value at multivariate analysis. 39 On the contrary, we found that Forns Score, Lok Index and PLF values above the viremic F4 cut-off were associated with an increased risk of HCC. Although these data have been obtained in a much selected cohort, thus preventing us from assessing NITs real predictive values, we think that this aspect needs further external large validation.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…These noninvasive score systems have also been shown a good prognostic value for prognosis of patients with chronic hepatitis C (CHC). 12 However, only a few studies in literature have evaluated prognostic value of NIFS for the long-term survival of PBC population.…”
Section: Introductionmentioning
confidence: 99%